Evaluation of Neurovascular Complication of Cervical Ribs - Gholamreza Dashti; Nazem Ghasemi (Negah Institute for Scientific Communication, 2015)
Introduction: Cervical rib is relatively uncommon congenital abnormality that originates from the seventh cervical vertebrae and rarely from the sixth vertebrae. The purpose of this paper is to consider that this abnormal condition is an important cause of neurovascular compression at the thoracic outlet. Methods: In this study all patients who were referred to radiology department of Isfahan hospitals (Iran) for chest X-ray or other cervical films, for any reasons, were evaluated for cervical rib and anyone who had this abnormality was entered in this study. Here, we performed Nerve Conduction Velocity Test (NCV) and Doppler sonography, depending on the vascular or neurological symptoms. Results: The results of this study show that the incidence of the neurological compression was higher than vascular compression. In addition, the prevalence of neurological complication in female was high (85.7%) and a significant percentage of them were above 30 years. Conclusion: Cervical rib occurs more commonly in women and have different prevalence rates in different ethnic populations. Moreover, a high percentage of them have neurological complication which is a symptom of thoracic outlet syndrome.